Fibromyalgia and Other Central Pain Syndromes. - Wallace, Daniel J. (Wolters Kluwer Health, 2005)
This volume is the first comprehensive text devoted to fibromyalgia and other centrally mediated chronic pain syndromes. Leading experts examine the latest research findings on these syndromes and present evidence-based reviews of current controversies. Chapters discuss the definition, epidemiology, and pathophysiology of chronic pain and fibromyalgia, the clinical presentations of fibromyalgia syndrome, and central sensitization syndromes associated with chronic neuromuscular pain. The contributors thoroughly examine various approaches to evaluation and management of patients with fibromyalgi.